Xpert® MTB/RIF assay: development, evaluation and implementation of a new rapid molecular diagnostic for tuberculosis and rifampicin resistance. (September 2011) - Lawn, Stephen D; Nicol, Mark P
Global TB control efforts have been severely hampered by the lack of diagnostic tests that are accurate, simple to use and can be applied at the point of clinical care. This has been further compounded by the widespread inability to test for drug resistance. The Xpert ® MTB/RIF assay is a rapid molecular assay that can be used close to the point of care by operators with minimal technical expertise, enabling diagnosis of TB and simultaneous assessment of rifampicin resistance to be completed within 2 h. Moreover, this can be accomplished using unprocessed sputum samples as well as clinical specimens from extrapulmonary sites. We review in detail the development of this assay, its evaluation within the laboratory, its utility among adult and pediatric TB suspects, its use as a screening tool for HIV-associated TB and studies of its implementation at the district and sub-district levels in resource-limited settings. Following endorsement by the WHO in 2010, we consider the next steps in the implementation of the assay and its potential impact in high burden settings.